Managing Pesticide Drift - Frederick M. Fishel; Jason A. Ferrell (EDIS)
PI232, a 17-page illustrated guide by F. M. Fishel and J. A. Ferrell, discusses factors influencing drift and provides common-sense solutions for minimizing potential drift problems. Published by the UF Department of Agronomy, September 2010.